A ideia de justiça na crise moral contemporânea - Campelo, Olívia Brandão Melo (2016)
This research was developed with the objective of seeking a way to accomplish the concept of justice in contemporary moral crisis. The society is experiencing an intense process of transformation of its values. In order to answer the inquiries of this uncertain moment, the contemporary legal philosophy focuses its discussions under the strands of liberalism and communitarianism. While the the liberalism understand that society is not governed by certain common goals applied to its members, but by just principles, which do not assume that a certain way of living is more correct than the other; communitarians believe that the experiences and meanings of individuals are shaped by the ideals of their home community, as an integrated part in the search for a common good. For the realization of this paper, It was necessary a tour in the history of legal philosophy and a brief analysis of the idea of Justice in Ancient Greece with Socrates, Plato and Aristotle; a passage through the Middle Ages to understand the lessons of Augustine, Aquinas and William Ockham; followed by a search for an idea of a more “modern” justice, with the influence of Kant in contemporary liberal thought and the opposition of Hegel to Kant's thought. Subsequently, the contractualist tradition was addressed by John Rawl´s theory of justice and his liberal view on the concept of justice. In regards to the communitarian objection to the liberal theory, especially to Rawls´, it was evaluated the diagnosis and contributions of Alasdair MacIntyre and Michael Sandel about moral decay and the idea of justice in the current context. It was concluded by the existence of moral crisis, considering also the crisis of values, as well as a legal crisis that compromises the ideal of justice. Thus, it becomes necessary an emergency resumption of practical rationality and the return of the theory of Aristotelian virtues as a way of carrying out the idea of justice